Naked barley: taxonomy, breeding, and prospects of utilization - K. A. Lukina; O. N. Kovaleva; I. G. Loskutov (Вавиловский журнал генетики и селекции)
This review surveys the current state of taxonomy, origin, and utilization prospects for naked barley. The cultivated barley Hordeum vulgare L. incorporates the covered and naked barley groups. Naked barleys are divided into six-row naked barley (convar. сoeleste (L.) A. Trof.) and two-row naked barley (convar. nudum (L.) A. Trof.). The groups include botanical varieties differing in the structural features of spikes, awns, floret and spikelet glumes, and the color of kernels. The centers of morphogenesis for naked barley are scrutinized employing archeological and paleoethnobotanical data, and the diversity of its forms. Hypotheses on the centers of its origin are discussed using DNA marker data. The main areas of its cultivation are shown, along with possible reasons for such a predominating or exclusive distribution of naked barley in highland areas. Inheritance of nakedness and mechanisms of its manifestation are considered in the context of new data in genetics. The biochemical composition of barley grain in protein, some essential and nonessential amino acids, β-glucans, vitamins, and antioxidants is described. Naked barley is shown to be a valuable source of unique combinations of soluble and insoluble dietary fibers and polysaccharides. The parameters limiting wider distribution of naked barley over the world are emphasized, and breeding efforts that could mitigate them are proposed. Pathogen-resistant naked barley accessions are identified to serve as promising sources for increasing grain yield and quality. Main stages and trends of naked barley breeding are considered and the importance of the VIR global germplasm collection as the richest repository of genetic material for the development of breeding is shown.